Lymphocyte apoptosis induced by CD95 (APO-1/Fas) ligand-expressing tumor cells: a mechanism of immune evasion? - Strand, Susanne; Hofmann, Walter J.; Hug, Hubert; Müller-Schilling, Martina; Otto, Gerd; Strand, Dennis; Mariani, Sara M.; Stremmel, Wolfgang; Krammer, Peter H.; Galle, Peter R. (Nature medicine, 1996)
The CD95 (APO-1/Fas) system is an important mediator of T-cell cytotoxicity. We investigated this system in 22 hepatocellular carcinomas (HCCs) from patients. All HCCs had partially or completely lost the expression of the CD95 receptor constitutively expressed by normal liver cells and might thus evade CD95-mediated killing. We also considered a new mechanism of immune evasion, namely, the active destruction of T-lymphocytes by tumor cells expressing CD95 ligand (CD95L). CD95L messenger RNA and protein could be detected in the HCCs. In coculture experiments, HepG2 hepatoblastoma cells, expressing CD95L mRNA after treatment with cytostatic drugs, killed CD95+ Jurkat lymphocytes. Our data suggest that tumor cells can evade immune attack by down-regulation of the CD95 receptor and killing of lymphocytes through expression of CD95L.